ANALISIS PENERAPAN PAJAK ATAS TRANSAKSI E-COMMERCE - Muhammad Hamdan; Isnani Yuli Andini (Universitas Widyatama, 2022)
This study aims to find out the general description, supporting factors and constraints of the application of taxes on e-commerce transactions in Indonesia. The method of data analysis in this study is to use a descriptive method. So the authors use the method of observation, interviews and documentation in collecting the data manually itself. And the results obtained in this study are that the perpetrators of E-Commerce transactions can also be categorized as tax subjects who have an obligation to pay taxes to the state. And there are several supporting factors in the application of taxes to e-commerce transactions, namely for the tax authorities: Data and information for taxpayers, then for taxpayers: Provision of facilities (infrastructure) for taxpayers in carrying out tax obligations, Expanding business in the field of e-commerce, and sales strategy. Apart from the supporting factors, of course there are also some obstacles experienced by the tax authorities, namely: There are still many e-commerce players who do not have a TIN, and the emergence of non-legal applications. And for taxpayers are: Lack of socialization, Little knowledge about taxes, Lack of awareness about tax developments, Fear of taxes.